P590The NO-donor SNAP exerts cardioprotection against ischemia/reperfusion injury in human embryonic stem cell-derived cardiomyocytes. (15th July 2014) - Paloczi, J; Varga V, Z; Apati, A; Szebenyi, N; Sarkadi, B; Madonna, R; Csont, T; Ferdinandy, P; Gorbe, A
Abstract: Drug screening platforms based on human stem cell (hESC)-derived cardiomyocytes can be used for screening of potential cardiocytoprotective agents. However, little is known on their behavior in simulated ischemia/reperfusion conditions. In this study we tested the cytoprotective effect of the NO-donor S-nitroso-N-acetyl-penicillamine (SNAP) and the particulate guanylate cyclase activator brain type natriuretic peptide (BNP) in hESCs differentiated to early cardiac lineage stage or to cardiomyocytes exposed to simulated ischemia/reperfusion injury. In the first set of experiments, hESC differentiated to early cardiac lineage cells were exposed to 150 min simulated ischemia in the presence of the NO-donor SNAP (10; 1; 0.1 μM), BNP (100; 10; 1 nM), and the non-specific NO synthase inhibitor Nω-Nitro-L-arginine (L-NNA, 10 μM). As a control experiment, other series of early cardiac lineage cells were maintained in normoxic condition for 150 min. All cells were subjected to simulated reperfusion for 120 min and viability was assessed by propidium iodine staining similarly to simulated ischemic groups. SNAP (at 10; 1 μM) significantly attenuated simulated ischemia/reperfusion-induced cell death of hESCs differentiated to early cardiac lineage, as compared to vehicle. However, simulated ischemia/reperfusion-induced cell death was not affected by BNP or by L-NNA. In separate experiments, the cardiocytoprotective effect of SNAP was also proven (at 1 μM) in hESC-derived cardiomyocytes, when cells were subjected to simulated ischemia/reperfusion. We conclude that SNAP but not BNP protects hESCs differentiated to either early cardiac lineage or to cardiomyocytes against simulated ischemia/reperfusion injury. The present hESC-derived cardiomyocyte-based screening platform is a useful tool for discovery of cardiocytoprotective molecules and their cellular mechanisms.